2014
DOI: 10.1021/cr400546e
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Sensors for Measuring Metal Ions in Living Systems

Abstract: CONTENTS 1. Introduction 4564 2. General Features of Fluorescent Sensors for Metal Ions 4566 2.1. Photophysical Properties of Fluorophores 4566 2.2. Mechanisms of Altering a Fluorescence Signal 4566 2.3. Classes of Sensors for Live-Cell Imaging 4568 2.3.1. Molecular Probes 4568 2.3.2. Genetically Encoded Probes 4568 2.3.3. Hybrid Probes 4569 3. Important Considerations for Introduction of Sensors 4569 3.1. Factors Affecting the Intracellular Concentration of Sensors 4569 3.2. Buffering 4570 3.3. Localization 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
1,210
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 2,184 publications
(1,235 citation statements)
references
References 340 publications
(621 reference statements)
8
1,210
0
17
Order By: Relevance
“…Two main families of FRET-based Zn 2+ sensors have been developed, namely the Zap-sensors by the Palmer group [51], and the eCALWYsensors by the Merkx group and ourselves [52]. Free cytosolic zinc concentrations measured using these FRET-sensors were approximately in the same range as those measured with chemical probes or hybrid sensors, and it is generally agreed now that free zinc is around a few hundreds of picomolar [53][54][55]. Both FRET sensor families have been targeted to intracellular organelles such as the ER, the nucleus, the mitochondria or the Golgi apparatus by in-frame fusion with suitable targeting motifs [51,[56][57][58].…”
Section: Free Zn 2+ Concentrations In the β Cellmentioning
confidence: 99%
“…Two main families of FRET-based Zn 2+ sensors have been developed, namely the Zap-sensors by the Palmer group [51], and the eCALWYsensors by the Merkx group and ourselves [52]. Free cytosolic zinc concentrations measured using these FRET-sensors were approximately in the same range as those measured with chemical probes or hybrid sensors, and it is generally agreed now that free zinc is around a few hundreds of picomolar [53][54][55]. Both FRET sensor families have been targeted to intracellular organelles such as the ER, the nucleus, the mitochondria or the Golgi apparatus by in-frame fusion with suitable targeting motifs [51,[56][57][58].…”
Section: Free Zn 2+ Concentrations In the β Cellmentioning
confidence: 99%
“…In contrast, the unsubstituted cerium sandwich complex, CePc 2 , which is known to contain a tetravalent (Ce 4+ ) cation, displays no appreciable absorption intensity in the 500 nm spectral region. 34,36 On the basis of this comparison, as well as other considerations, the authors concluded that in solution the Ce 4+ oxidation state dominates for the Ce(15c5Pc) 2 complex, but upon the formation of monolayers, IET leads to the Ce 3+ oxidation state predominating.…”
Section: Intramolecular Et Systemsmentioning
confidence: 91%
“…Depending on the substitution pattern of the tetrapyrrolic ligands bound to the cerium metal, overall neutral complexes but differing in the oxidation state of cerium and hence the charge on the ligand, have been reported. 36 Selektor and coworkers studied the physicochemical properties of Langmuir-type monolayer films of Ce(15c5Pc) 2 . The absorption spectrum of the Ce(15c5Pc) 2 film (recorded by differentialreflection absorption spectrometry) was substantially different from that of the chloroform solution from which it was cast (Fig.…”
Section: Intramolecular Et Systemsmentioning
confidence: 99%
See 2 more Smart Citations